Correlation of Moderate-Intensity Physical Exercise on Irisin, Oxidized-LDL and HDL Level in ≥50 Years Old Obese Men - Made Putra Semadhi; Melisa Intan Barliana; Dewi Muliaty; Andi Wijaya (The Prodia Education and Research Institute (PERI), 2019)
BACKGROUND: Irisin is secreted by our muscle during physical exercise, which has been recently studied to be linked with lipid metabolism. The aim of this study was to investigate the role of irisin that interact with the oxidized-low density lipoprotein (ox-LDL) and high density lipoprotein cholesterol (HDL-C) levels that are affected by moderate intensity exercise in obese men aged ≥50 years.METHODS: This was a cross-sectional study with 70 obese men whose age ≥50 years old as participants. Participants were classified into two groups of men with and without physical exercised, based on American College of Sports Medicine (ACSM). Irisin and ox-LDL plasma levels were analyzed using enzyme-linked immunosorbent assay (ELISA), meanwhile the HDL-C serum level was analyzed using homogenous enzymatic methods.RESULTS: The result showed an association between the duration of physical exercise per week and irisin level (R=0.584, p<0.01), also between the duration of physical excercise per week and ox-LDL level (R=-0.274, p<0.05). Meanwhile, there was a negative association between irisin levels and ox-LDL (R=-0.294, p<0.05). Irisin indicated to be correlated with HDL-C (R=0.215, p>0.05).CONCLUSION: Moderate-intensity physical exercise may decrease cardiovascular risk and improve the quality of life among obese subjects aged ≥50 years old, which was indicated by the decrease of ox-LDL and the increase of irisin level. In addition, it can be concluded that the higher the irisin level showed the lower levels of ox-LDL and higher level of HDL-C.KEYWORDS: obesity, elderly, irisin, ox-LDL, HDL-C, physical exercise